Assessment of in vitro interferon-gamma responses from peripheral blood mononuclear cells of cattle infected with Mycoplasma mycoides ssp. mycoides small colony type - Jores, Joerg; Nkando, I.; Sterner-Kock, Anja; Haider, W.; Poole, Elizabeth J.; Unger, H.; Muriuki, C.; Wesonga, H.O.; Taracha, E.L.N. (Elsevier, 2008)
Contagious bovine pleuropneumonia (CBPP) is a lung disease caused by the bacterial pathogen Mycoplasma mycoides ssp. mycoides small colony type (MmmSC). It has been spreading due to a number of factors including poor vaccine efficacy and poor sensitivity of current diagnostic tests. The purpose of this study was to assess interferon gamma (IFN-gamma) release after stimulation of peripheral blood mononuclear cells (PBMC) from experimentally infected cattle. PBMC collected from 15 artificially infected animals were incubated with different concentrations of total MmmSC antigen. After 72h of incubation the IFN-gamma release was measured and found to be elevated in 11 animals. We did not observe a correlation between IFN-gamma release of animals with and without pathomorphological gross lesions. Therefore, our data do not confirm a role for CD4 T-lymphocytes in protection, since there is no correlation between IFN-g secretion (supposed to be mainly derived from CD4 T-cells) and disease severity. Additionally, we applied immunocytochemistry on affected lung tissue and detected no build up of T-lymphocytes (CD4 T-cells, CD8 T-cells) but a high presence of myeloid cells.